The trickle-down effect of empowering leadership: a boundary condition of performance pressure. Issue 3 (20th March 2020) - Byun, Gukdo; Lee, Soojin; Karau, Steven J.; Dai, Ye
Abstract : Purpose: By taking a social learning perspective, this study examines the trickle-down effect of empowering leadership across hierarchical levels in an organization. Specifically, this study aims to demonstrate that the empowering leadership of higher-level leaders promotes the task performance of employees through the mediation of the empowering leadership of lower-level leaders. It also seeks to confirm the role of performance pressure as a boundary condition in social learning process. Design/methodology/approach: Under a moderated mediation framework, this study tests our hypotheses through a hierarchical regression analysis. The data used in the analysis is from the survey responses of 209 subordinate-supervisor dyads. Findings: This study finds that the empowering leadership of higher-level leaders promotes the empowering leadership of lower-level leaders, which indirectly improves the task performance of employees. It also finds that performance pressure perceived by lower-level leaders moderates the relationship between the empowering leadership of higher- and lower-level leaders, thus moderating the proposed indirect effect. Research limitations/implications: This study complements the findings of previous studies by identifying the trickle-down effect of empowering leadership across different hierarchical levels in an organization and by highlighting its boundary condition. In addition, this study provides evidence for the presence of trickle-down effect of leadership in an Eastern culture. Practical implications: This study suggests the necessity of leadership education and training programs within organizations by revealing the importance of social learning process for promoting empowering leadership. In addition, it also suggests that performance pressure in an organization not only dampens empowering leadership but also has a negative effect on the task performance of employees. Originality/value: This study demonstrates the influence mechanism of empowering leadership through a systematic verification of its trickle-down effect, which has been lacking in previous studies. It also highlights the moderating role of performance pressure, as a contextual factor, in the social learning and influence process of empowering leadership.